Water Quality and Productivity of Dryland Catfish Pond Based on Existing Technology and Land Priority in Gunungkidul - Septriani, Nur Indah; Rustadi, Rustadi (Indonesian Aquaculture Society (MAI), 2015)
This research is aimed to examine the water quality and productivity of dryland catfish pond based on the existing technology and land priority in Gunungkidul and to determine the suitable technology based on the land priority. Samples from the ponds employing intensive, extensive, and semi-intensive technology were analysed to find out the water quality such as the ammonia, nitrate, and nitrite contents; pH; DO; temperature and turbidity; land productivity; and profit. Existing analysis used scoring of sample ponds which included water quality, productivity and profit analysis. The highest score of the sample ponds becomes the sample of technology applied in the certain area. The highest score in high priority land was PTI (79%), medium priority land was PSS (72%), and non-priority land was NPE (68%). The water quality, productivity and profit in high priority land reached optimal result when it used intensive technology. The water quality, productivity and profit in medium priority land reached optimal result when it used semi-intensive technology. The water quality, productivity and profit in non-priority land reached optimal result when it used extensive technology.Keywords: Water quality; productivity; scoring; dryland catfish pond; existing technology; land priority